2015
DOI: 10.1080/15374416.2014.971460
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Callous-Unemotional Traits in Preschool Children With Disruptive Behavior Problems Using Peer Reports

Abstract: The goal of this study was to examine the extent to which preschoolers with externalizing behavior problems (EBP) can identify behaviors indicative of callous-unemotional (CU) traits among their peers. Participants for this study included 86 preschool children (69% boys; Mage = 5.07 years) with at-risk or clinically elevated levels of EBP who were attending a summer treatment camp. Data collected from the children, their peers, and the counselors who worked at the summer camp examined preschoolers' social pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
3
21
1
Order By: Relevance
“…For example, Graziano et al. () found that preschool children higher in callousness evidenced poorer school readiness across academic, behavioral, and social domains of adjustment. However, the predominant use of cross‐sectional designs in examining links between callousness and school adjustment problems do not authoritatively test our mediational hypotheses.…”
Section: Callousness As a Mediator Of Family Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Graziano et al. () found that preschool children higher in callousness evidenced poorer school readiness across academic, behavioral, and social domains of adjustment. However, the predominant use of cross‐sectional designs in examining links between callousness and school adjustment problems do not authoritatively test our mediational hypotheses.…”
Section: Callousness As a Mediator Of Family Instabilitymentioning
confidence: 99%
“…In fact, Carlson et al (2015) found that callous-unemotional behaviors mediated associations between retrospective reports of child maltreatment and concurrent risky behaviors in late adolescence. Likewise, studies have also identified associations between callousness and children's school adjustment difficulties in early (Graziano et al, 2016) and middle childhood (Ciucci, Baroncelli, Franchi, Golmaryami, & Frick, 2014;Vaughn et al, 2011). For example, Graziano et al (2016) found that preschool children higher in callousness evidenced poorer school readiness across academic, behavioral, and social domains of adjustment.…”
Section: Callousness As a Mediator Of Family Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of CU traits, the 5 th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; American Psychiatric Association, 2015) now includes a specifier to identify individuals with conduct disorder and CU traits. CU traits have been documented from early childhood (Graziano et al, 2016) into early adulthood (Byrd et al, 2013). However, little work has specifically examined the impact of CU on functioning in young adulthood, and the few existing studies have shown contrasting findings (Bartol and Miller, 2014; Byrd et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, CU traits were not associated with quality of life (QoL) in a clinical sample of youths with CD [ 22 ]. Impairment in youths with CP showed either no [ 19 , 22 , 29 , 30 ] or a positive [ 15 , 25 ] relationship with CU traits. In community samples high CU traits were associated with more global impairment [ 10 , 34 , 43 ], not only in the CD subsample, but in the no CD/high CU subsample as well [ 34 ].…”
Section: Introductionmentioning
confidence: 99%